Theoretical study of thieno[3,4-b]pyrazine derivatives with enhanced NLO response - Gester, Rodrigo; Torres, Alberto [UNESP]; da Cunha, Antonio R.; Andrade-Filho, Tarciso; Manzoni, Vinícius (Elsevier, 2021)
The study of new organic chromophores with improved NLO response aiming at a wide range of feasible applications has become a relevant and promising study area. In this context, a theoretical investigation of the NLO parameters of a series of π-conjugated chromophores derived from thieno[3,4-b]pyrazine is performed using the Time-Dependent Density Functional Theory with a frequency-dependent formalism. The results show that the studied chromophores can have enhanced NLO response. Consequently, the thieno[3,4-b]pyrazine derivatives can be considered suitable for various optoelectronic and photonic applications.
Keywords: DFT; NLO; Optical materials; Reactivity descriptors